The deteminants of Outward Direct Investment from China to Asia - Chen, Xiaoting (Universiti Malaysia Sarawak (UNIMAS), 2014)
This study examines the determinants of Outward Direct Investment (ODI) from China to Asia over ten year period starting form year 2003 to 2012 where the sample period is dictated by data availability. Including Levin, Lin and Chu (LLC), Im, Pesaran and Shin (IPS) and Fisher-type (Fisher-ADF and Fisher-PP) Panel unit root tests, and Pedroni‘scointegration test and Panel data estimation are employed in this study. The results show that there exists long-run relationship between the selected independent variable and China‘s ODI. Besides, the distance from China‘s capital Beijing to host country‘ capital is significant but negative to China‘s ODI. Furthermore, market-seeking FDI maybe not the main reason for Chinese investors to invest in Asia.